A novel candidate frameshift mutation for catecholaminergic polymorphic ventricular tchycardia - Işık, Fatma Büşra; Sözügüzel, Mavi Deniz; Genç, Nimetullah Mete; Çaralan, E. F.; Doğru, Zübeyir; Akdeniz, Coşkun; Tuzcu, Volkan; Cangül, Hakan (Nature Publishing Group, 2019)
[Abstract Not Available]
Conference: 51st Conference of the European-Society-of-Human-Genetics (ESHG) in conjunction with the European Meeting on Psychosocial Aspects of Genetics (EMPAG) Location: Milan, ITALY Date: JUN 16-19, 2018
Keywords: Catecholaminergic; Polymorphic; Ventricular Tachycardia